2006
DOI: 10.1073/pnas.0600263103
|View full text |Cite
|
Sign up to set email alerts
|

Mapping epitopes and antigenicity by site-directed masking

Abstract: Here we describe a method for mapping the binding of antibodies to the surface of a folded antigen. We first created a panel of mutant antigens (␤-lactamase) in which single surface-exposed residues were mutated to cysteine. We then chemically tethered the cysteine residues to a solid phase, thereby masking a surface patch centered on each cysteine residue and blocking the binding of antibodies to this region of the surface. By these means we mapped the epitopes of several mAbs directed to ␤-lactamase. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…Moreover, the binding site of GAD65 for antibodies displays greater polarity and more negatively charged amino acid residues on its surface whereas for GAD67 the C-terminal exhibits a subdued, neutral electrostatic field and hence possesses less polarity [50]. Finally, the C-terminal and catalytic loop residues of GAD65 display more flexibility and mobility than their GAD67 counterparts [30], recalling here that Paus and Winter [51] suggested that increases in protein flexibility and charge were associated with augmented protein antigenicity. Thus differing structural properties of the two GAD isoforms would explain at least to some degree why, for T1D sera, only the GAD65 isoform is independently autoantigenic.…”
Section: Antibody Epitopes In Sps and T1dmentioning
confidence: 66%
“…Moreover, the binding site of GAD65 for antibodies displays greater polarity and more negatively charged amino acid residues on its surface whereas for GAD67 the C-terminal exhibits a subdued, neutral electrostatic field and hence possesses less polarity [50]. Finally, the C-terminal and catalytic loop residues of GAD65 display more flexibility and mobility than their GAD67 counterparts [30], recalling here that Paus and Winter [51] suggested that increases in protein flexibility and charge were associated with augmented protein antigenicity. Thus differing structural properties of the two GAD isoforms would explain at least to some degree why, for T1D sera, only the GAD65 isoform is independently autoantigenic.…”
Section: Antibody Epitopes In Sps and T1dmentioning
confidence: 66%
“…The molecular identification in the remaining studies hinges on RT-PCR analyses and immunohistochemical localization, using antibodies directed against the transporter (14,15,18,21,31,32,37). The use of antibodies depends on immunoreactivity, which can be influenced by several factors, including the conformation of the antigen, phosphorylation, or masking from other structures (14,23,25). Furthermore, eventual splice variants without the targeted epitope will not be immunoreactive.…”
mentioning
confidence: 99%
“…33 In summary, we have shown how an antibody can inhibit enzyme activity hyperbolically by constraining conformation change. In view of the apparent correlation between antigenicity and epitope flexibility, 34 we anticipate that this mechanism will recur in allosteric effector antibodies that modulate the activities of other enzymes and receptors.…”
Section: Discussionmentioning
confidence: 99%